Evaluation of Ratoon Management Practices for Cane Yield and Juice Quality of Sugarcane Ratoon - Parajuli, Tulsi; Marahatta, Santosh; Amgain, Lal Prasad; Dhakal, Shiva Chandra (Journal of Agriculture and Forestry University, 2026)
Sugarcane is an important industrial crop in Nepal. Low plant population in ratoon crops is a major constraint that reduces cane number and lowers yield. An experiment was conducted in Nawalparasi (west) to evaluate effect of different ratoon management strategies on cane yield and juice quality of sugarcane. A two-factor randomized complete block design was employed to evaluate two fertilizer placement methods (band placement and broadcasting) in combination with seven ratoon management practices: control (M1), earthing up (M2), stubble shaving (M3), M2 + M3 (M4), M4 + off-barring (M5), trash mulching (M6), and M5 + M6+ Trichoderma (M7), replicated thrice. Results showed non-significant effect of both the factors on cane length, cane diameter, millable canes and single cane weight. Interaction effect was significant on millable canes and cane yield where combined ratoon management practices (M7) along with band placement of fertilizers recorded the highest value. Major quality traits remain unaffected due to treatments. Sugar yield (5.88 t/ha) from band placement was superior to broadcasting. Also, combined ratoon management practices (M7) resulted the highest sugar yield (6.45 t/ha) while being at par with M6 and M5. Those findings suggested integrated ratoon management strategies for better cane yield and juice quality.